Proceedings of the 2018 Conference on Empirical Methods in Natural Language Processing 2018
DOI: 10.18653/v1/d18-1103
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Adaptation of Neural Machine Translation to New Languages

Abstract: This paper examines the problem of adapting neural machine translation systems to new, low-resourced languages (LRLs) as effectively and rapidly as possible. We propose methods based on starting with massively multilingual "seed models", which can be trained ahead-of-time, and then continuing training on data related to the LRL. We contrast a number of strategies, leading to a novel, simple, yet effective method of "similar-language regularization", where we jointly train on both a LRL of interest and a simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
192
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 165 publications
(200 citation statements)
references
References 18 publications
8
192
0
Order By: Relevance
“…Artificial noises for the source sentences are used to counteract word-by-word training data in unsupervised MT (Artetxe et al, 2018c;Lample et al, 2018a;Kim et al, 2018), but in this work, they are used to regularize the NMT. Neubig and Hu (2018) study adapting a multilingual NMT system to a new language. They train for a child language pair with additional parallel data of its similar language pair.…”
Section: Related Workmentioning
confidence: 99%
“…Artificial noises for the source sentences are used to counteract word-by-word training data in unsupervised MT (Artetxe et al, 2018c;Lample et al, 2018a;Kim et al, 2018), but in this work, they are used to regularize the NMT. Neubig and Hu (2018) study adapting a multilingual NMT system to a new language. They train for a child language pair with additional parallel data of its similar language pair.…”
Section: Related Workmentioning
confidence: 99%
“…A common challenge in applying natural language processing (NLP) techniques to low-resource languages is the lack of training data in the languages in question. It has been demonstrated that through cross-lingual transfer, it is possible to leverage one or more similar high-resource languages to improve the performance on the low-resource languages in several NLP tasks, including machine score(L tf,1 , L tk ) score (L tf,2 , L tk translation (Zoph et al, 2016;Johnson et al, 2017;Nguyen and Chiang, 2017;Neubig and Hu, 2018), parsing (Täckström et al, 2012;Ammar et al, 2016;Ahmad et al, 2019;, partof-speech or morphological tagging (Täckström et al, 2013;Cotterell and Heigold, 2017;Malaviya et al, 2018;Plank and Agić, 2018), named entity recognition (Zhang et al, 2016;Mayhew et al, 2017;Xie et al, 2018), and entity linking (Tsai and Roth, 2016;Rijhwani et al, 2019). There are many methods for performing this transfer, including joint training (Ammar et al, 2016;Tsai and Roth, 2016;Cotterell and Heigold, 2017;Johnson et al, 2017;Malaviya et al, 2018), annotation projection (Täckström et al, 2012;Täckström et al, 2013;Zhang et al, 2016;Plank and Agić, 2018), fine-tuning (Zoph et al, 2016;Neubig and Hu, 2018), data augmentation (Mayhew et al, 2017), or zero-shot transfer (Ahmad et al, 2019;Xie et al, 2018;Neubig and Hu, 2018;Rijhwani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2 In this section, we demonstrate the types of analysis that are provided by this standard usage of compare-mt. Specifically, we use the example of comparing phrase-based (Koehn et al, 2003) and neural (Bahdanau et al, 2015) Slovak-English machine translation systems from Neubig and Hu (2018).…”
Section: Compare-mt Ref Sys1 Sys2mentioning
confidence: 99%